(untitled) (Global Journal of Science Frontier Research, 2018)
Kutki (Picrorhiza kurroa Royle ex Benth.) is an important medicinal plant used in various herbal drug formulations possessing hepatoprotective activity. The pharmacological importance of this species has been demonstrated due to the presence of iridoid glycosides, such as picroside-I and picroside-II in underground part. In the present study, fresh roots and rhizomes collected from 2600m to 3300m altitude of Himachal Pradesh (Rohtang area) were used and extract yield, phytochemical constituents, namely picroside-I and picroside-II, of water and methanol extracts prepared using four different extraction methods viz. soxhlet, extraction by refluxing, microwave assisted extraction and sonication assisted extraction were compared for the standardization of extraction methods of picroside-I and picroside-II. Sonication assisted extraction for 36 minutes with methanol as solvent yielded 44.269 per cent extract with 6.825 per cent picroside-I and 5.291 per cent picroside-II content, which was better in comparison to other methods regarding time consumption and yield.